CC-004 Unexpected cause of colitis in a middle-aged Caucasian female. (23rd September 2015) - Isse, S; Lambo, D; Mangera, Z; Krishnan, B; Lindo, D
Abstract : Introduction: We report on a common clinical problem with an unexpected aetiology in a middle aged Caucasian female. Methods: N/A. Results: The initial blood results were unremarkable apart from a CRP of 145 and albumin of 27. A plain abdominal x-ray showed extensive distal colon wall oedema. The patient went on to have a flexi-sigmoidoscopy, which demonstrated a congested recto-sigmoid mucosa with two discrete ulcers and florid, tender anal tags. Overall, the appearances were suggestive of a diagnosis of Crohn's and the patient was continued on intravenous steroids and pentasa. Biopsies taken proved indeterminate. However, the CRP continued to increase, peaking at 304, the albumin continued to fall and the symptoms persisted. Failure to respond to treatment prompted alternative causes to be investigated. All seven stool specimens sent for microscopy and cultures were positive for leucocytes but failed to isolate any infective causes. Amoebic serology was also negative. Conclusion: This unusual case highlights the need for a thorough history, including travel and sexual history, in any patient presenting with chronic diarrhoea in order to avoid delay in diagnosis and minimise the risk of further transmission. Furthermore, vigilance is required when reviewing the response to treatment in a newly diagnosed colitis. Finally, unusual endoscopic appearance should be biopsied and sent to microbiology in addition to pathology.